2011
DOI: 10.1080/00103624.2011.542219
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Induced Growth and Yield Enhancement in Two Wheat Genotypes Differing in Salinity Tolerance

Abstract: Silicon (Si) is known to alleviate a number of abiotic stresses in higher plants including salinity stress.Two independent experiments were conducted to evaluate the role of Si in alleviating salinity stress in two contrasting wheat (Triticum aestivum L.) genotypes, Auqab-2000' (salt sensitive) and SARC-3 (salt tolerant). In the first experiment, genotypes were grown in hydroponics with two levels of salinity (0 and 60 mM NaCl) with and without 2 mM Si in a completely randomized design with four replications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…With respect to the interactive effect between inoculating AM, as well as salinity levels and phosphorus application, inoculating AM under any level of salinity with using phosphorus fertilization had no significant effect on Na % in wheat shoots and roots during 1 st and 2 nd stage of planting. Obtained results are in agreement with those obtained by Ali et al, (2000), Akbarimoghaddam et al, (2011), Tahir et al, (2011) Also, Abdel-Fattah and Asrar (2012) Mycorrhizal colonization of a plant with AMF can reverse the effect of salinity on K + and Na + Nutrition. Mycorrhizal colonization can enhance K + absorption under saline conditions Alguacil et al, (2003); Giri et al, (2003) and Zuccarini and Okurowska (2008) while preventing Na + translocation to shoot tissues.…”
Section: Sodium Concentration In Wheat Shoots and Rootssupporting
confidence: 91%
“…With respect to the interactive effect between inoculating AM, as well as salinity levels and phosphorus application, inoculating AM under any level of salinity with using phosphorus fertilization had no significant effect on Na % in wheat shoots and roots during 1 st and 2 nd stage of planting. Obtained results are in agreement with those obtained by Ali et al, (2000), Akbarimoghaddam et al, (2011), Tahir et al, (2011) Also, Abdel-Fattah and Asrar (2012) Mycorrhizal colonization of a plant with AMF can reverse the effect of salinity on K + and Na + Nutrition. Mycorrhizal colonization can enhance K + absorption under saline conditions Alguacil et al, (2003); Giri et al, (2003) and Zuccarini and Okurowska (2008) while preventing Na + translocation to shoot tissues.…”
Section: Sodium Concentration In Wheat Shoots and Rootssupporting
confidence: 91%
“…In contrast, foliar and soil Si treatments significantly decreased leaf K concentrations compared with the untreated control. In wheat, Tahir et al (2011) found that the addition of Si to irrigated saline water significantly improved K uptake. Kamenidou et al (2008) concluded that there were no differences in the leaf macronutrients (N, P, K, Mg, and Ca), and micronutrients (Al, B, Fe, Na, and Zn) between Si treatments and the control in ornamental sunflower (Helianthus annuus L.).…”
Section: Resultsmentioning
confidence: 99%
“…Soil salinity generally prevails in arid to semiarid regions around the globe and is among the main causes for reduction of food production. Soil salinity causes physiological drought and ionic toxicity to plants (Acosta-Motos et al 2015) hampering growth and yield of plants (Tahir et al 2011). A number of metabolic and physiological adaptations/mechanisms have been reported in plants to cope with salinity stress (Ashraf et al 2010, Tahir et al 2012.…”
Section: Introductionmentioning
confidence: 99%